Предупреждение межличностных конфликтов в коллективе школьников-подростков - Дурманенко, Евгения Аристарховна; Durmanenko, Yevheniia A. (Східноєвропейський національний університет імені Лесі Українки, 2013)
В статье раскрываются условия предупреждения конфликтов среди школьников-подростков, а именно акцентируется внимание на формировании конфликтологической компетентности педагогов, положительно качественной адаптации подростков в учебно-познавательной деятельности, развитии их социально-коммуникативной активности и создании творческой учебно-воспитательной среды в общеобразовательной школе. The article describes the conditions for conflict prevention among school adolescents, particularly forming of conflictological competence of teachers which focuses on positive qualitative adaptation of adolescents in educational and cognitive activity, the development of their social and communicative activity and establishing of a creative educational atmosphere in secondary school
Prevention of interpersonal conflicts in a teenagers groups
Keywords: подросток; межличностные конфликты; конфликтологическая компетентность педагога; адаптация подростка в школе; социально-коммуникативная активность личности; teenager; interpersonal conflicts; conflictological competence of a teacher; adaptation of a teenager in school; social and communicative activity of a person